Performance evaluation of policies and programs accordance with guide prepared by a dutch court of audit and the board of supreme audit (case study in wasit state company for textile industries) - سعيد سناء عبدالرحيم; خنجر حيدر حسن (Journal of Economics and Administrative Sciences, 2016)
Abstract preparation process of performance evaluation in organizations is of extreme importance, and under development in organizations and the opening of markets and technological developments in the industry and heightened competition among industrial organizations imposed systems are built for performance give a clear picture about performance and competition, And centered research problem in answering the following questions: Is performance evaluation system is available in Wasit State Company for Textile Industries(Research sample ), This research aims to assess the performance of policies and programs in the company, according to guide performance evaluation of programs and policies prepared by the Dutch Court of audit and the Board of Supreme Audit , to identify and promote the positive points and negative points to reduce or overcome, and reflected the importance of search through deeper objective performance evaluation of policies and programmes in Wasit State Company for Textile Industries in accordance with the Guide to performance evaluation of programs and policies for access to scientific knowledge and the real and substantive positive and negative impacts on policies and programmes and their implementation and impact Outputs and the extent to which proficiency the objectives sought to be achieved, perhaps about problematic adopted Finder descriptive to complete theoretical research while the case study approach was adopted (Case Study) to complete the practical side, and reached several conclusions that policies formulated by the company during the calendar years have not been sufficient to mitigate the losses cascading through increasing revenues and reducing expenditures and There is no significant development in the company’s activity, both in the production process or on marketing and sales level, search reached a set of Recommendations was working on a comprehensive policy by the company, in coordination with all concerned ministries and provincial Council, and drafted realistically and accurately based on information and data are truthful and correct lead to increased chances of success and achieve expected benefits (limitation of consecutive losses) when implementing and reduce the risk of failure to the lowest possible